Concurrent context-free grammars - Mavlankulov, Gairatzhan; Othman, Mohamed; Selamat, Mohd Hasan; Turaev, Sherzod (Springer Science+Business Media Singapore, 2014)
In this paper we study some properties of context-free concurrent grammars which are controlled by Petri nets under parallel firing strategies, i.e., the transitions of a Petri net fire simultaneously in different modes. These variants of control increase the computational power of generative devices. Moreover, they can be used as theoretical models for parallel computing devices.